2007
DOI: 10.3168/jds.2006-800
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Selenium Concentration in Milk: Effects of Amount of Selenium from Yeast and Cereal Grain Supplements

Abstract: Two experiments were conducted to establish responses in milk Se concentrations in grazing dairy cows to different amounts of dietary Se yeast, and to determine the effects of the Se concentration of the basal diet. The hypothesis tested was that the response in milk, blood, and tissue Se concentrations to supplemental Se would not be affected by whether the Se was from the basal diet or from Se yeast. In addition, by conducting a similar experiment in either early (spring; experiment 1) or late (autumn; exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
48
2
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 17 publications
(22 reference statements)
19
48
2
2
Order By: Relevance
“…Our data showed a maximum level (about twofold higher than the control) already at day 3, with plateau at day 10 until the end of the trial (Figure 1b), whereas in previous works, the selenium concentrations in milk and plasma tend to remain at steady condition in about 1 to 2 weeks after supplementation (Heard et al, 2007) and reach their maximums in about 40 days (Conrad and Moxon, 1979). Givens et al (2004) report a linear relationship between milk and dietary selenium concentrations in which the milk selenium (mg/l) 5 8.03 1 12.04 diet selenium (mg/kg DM) with an r 2 5 0.96.…”
Section: Discussioncontrasting
confidence: 66%
“…Our data showed a maximum level (about twofold higher than the control) already at day 3, with plateau at day 10 until the end of the trial (Figure 1b), whereas in previous works, the selenium concentrations in milk and plasma tend to remain at steady condition in about 1 to 2 weeks after supplementation (Heard et al, 2007) and reach their maximums in about 40 days (Conrad and Moxon, 1979). Givens et al (2004) report a linear relationship between milk and dietary selenium concentrations in which the milk selenium (mg/l) 5 8.03 1 12.04 diet selenium (mg/kg DM) with an r 2 5 0.96.…”
Section: Discussioncontrasting
confidence: 66%
“…Although these results confirm earlier studies by numerous workers including Givens et al (2004), Juniper et al (2006) and Heard et al (2007), milk yield responses to Se supplementation have been noted in New Zealand from cows grazing low-Se pastures (Grace et al, 1997). However, in the current study there was a significant (P , 0.05) positive linear effect of increasing Se supplied in the form of SY.…”
Section: Feed Analysessupporting
confidence: 57%
“…Recent work by Heard et al (2007) emphasised that if the objective was to produce highSe products for human consumption then it was important that they are produced in a consistent and predictable manner. While their work showed a very rapid increase in milk Se concentration, which peaked after 7 to 15 days of Se supplementation, the current study in which Se analyses started only after 28 days of supplementation showed that milk Se concentration peaked much later, between 84 and 112 days after treatment initiation.…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CTR group cows had an higher milk Se/ingested Se ratio compared with the 3.2% reported by Calamari et al (2010). On the other hand, average Se secretion in milk of cows supplemented with selenized yeast is expected to be 10-18% depending on lactation stage, milk yield, protein yield, and Se intake (Heard et al, 2007;Juniper et al, 2008; Figure 1 Behavior of total Se in milk (a), plasma (b), and feces (c) in dairy cows that received diets containing either sodium selenite providing Se at 0.3 mg/kg DM (CTR) or microencapsulated sodium selenite providing Se at 0.3 mg/kg and 0.5 mg/kg DM (0.3M and 0.5M, respectively) and selenized yeast providing Se at 0.3 mg/kg and 0.5 mg/ kg DM (0.3Y and 0.5Y, respectively). Values are least squares means, and vertical bars represent s.e.…”
Section: Resultscontrasting
confidence: 45%